0324 sleep duration and brain MRI biomarkers: results from SOL-INCA MRI study. (25th May 2022) - Gonzalez, Kevin; Tarraf, Wassim; Stickel, Ariana; Kaur, Sonya; Agudelo, Christian; Cai, Jianwen; Gallo, Linda; Testai, Fernando; Redline, Susan; DeCarli, Charles; Gonzalez, Hector
Abstract: Introduction: Long and short sleep have been associated with stroke and dementia. Sleep patterns may differ by sex and Hispanic/Latino background. Within Hispanics/Latinos heterogeneity in sleep outcomes exists and is understudied. The purpose of this study was to examine associations between sleep duration and MRI biomarkers of brain health. Methods: SOL-Investigation of Neurocognitive Aging (SOL-INCA) MRI study is an ongoing ancillary study of the Hispanic Community Health Study/Study of Latinos (HCHS/SOL). Our analytic sample consisted of 1, 103 adults 50-years and older from diverse Hispanics/Latino backgrounds that completed baseline sleep assessments (2008-2011) and underwent neuroimaging (2018-ongoing; Mean age 64 ±6.9 years). The main exposures were baseline self-reported average nightly sleep duration. Outcomes included brain volume measures residualized for cranial volume (e.g. total brain, hippocampal, and white matter hyperintensities). Brain outcomes were modeled, using regression techniques, as a function of sleep duration and adjusting for age, sex, education, Hispanic/Latino background, language use, self-reported cardiovascular events, BMI, depressive symptoms, Apena/Hypopena index and self-reported sleep quality. Results: Mean sleep duration was 7.7 ± 1.36 hours, and 13.2% reported sleeping >9 hours. Increasing sleep duration was associated with smaller total brain (Btotal_brain -1.32 [-2.33 ; -0.32], p<0.05) per hour increment and larger lateral ventricle volumes (Blateral_ventricle=0.02 [~0.00; 0.04], p<0.05) after adjusting for sociodemographic, behavioral, cardio-vascular and sleep quality characteristics. The associations were not modified by sex or Hispanic/Latino background. Conclusion: We found that increments in sleep duration was associated with lower total brain volume and larger ventricle size, MRI measures that could associate with increased dementia-risk in diverse Hispanic/Latino adults. Support (If Any): This work is supported by National Institute on Aging (R01AG048642, RF1AG054548, and R01AG063868) and by the National Heart Lung Blood Institute (R01HL098297). Dr. González also receives additional support from P30AG59299. The Hispanic Community Health Study/Study of Latinos was carried out as a collaborative study supported by contracts from the National Heart, Lung, and Blood Institute (NHLBI) to the University of North Carolina (N01-philip glass beck HC65233), University of Miami (N01-HC65234), Albert Einstein College of Medicine (N01-HC65235), Northwestern University (N01-HC65236), and San Diego State University (N01-HC65237). The following Institutes/Centers/Offices contribute to the HCHS/SOL through a transfer of funds to the NHLBI: National Institute on Minority Health and Health Disparities, National Institute on Deafness and Other Communication Disorders, National Institute of Dental and Craniofacial Research, National Institute of Diabetes and Digestive and Kidney Diseases, National Institute of Neurological Disorders and Stroke, NIH Institution-Office of Dietary Supplements.